Inventarisasi Tumbuhan Famili Myrtaceae Di Kampung Andir, Rt.01/Rw.08, Desa Rancamulya, Sumedang - Alika Maulidina Rahma; Anisa Zahra; Ateng Supriatna (Lembaga Pengembangan Kinerja Dosen, 2023)
Myrtaceae is one of the largest families, numbering 5500 species. General characteristics of this family include taproots, woody stems, thin skin, shrubs, tannins, single leaves, and flat leaf edges. The fruit is in the form of tubers, tops, capsules and drupes. The purpose of this study was to determine the types of plants belonging to the Myrtaceae and to determine the morphology and distribution of the Myrtaceae family. The research was conducted on June 12 2023 in Andir Village, RT.01 / RW.08, Rancamulya Village, Sumedang Utara District, Sumedang Regency. The method used is the method of exploration and observation by exploring the research location while observing the surrounding plants. The species results obtained included Syzygium aqueum totaling 4 individuals, Syzygium polyanthum totaling 6 individuals, Syzygium myrtifolium Walp totaling 176 individuals and Psidium guajava L totaling 7 individuals.